ANALISIS OF GROSS AND NET ENROLLMENT RATES IN PRIMARY EDUCATION IN SULAWESI : CHALLENGES AND STRATEGIC DIRECTIONS FOR IMPROVING EDUCATIONAL ACCESS - Nadia Nurfikriah; Taufani Chusnul Kurniatun; Eka Prihatin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to analyze the trends and disparities in the Gross Enrollment Rate (GER) and Net Enrollment Rate (NER) in primary education across the Sulawesi region from 2014 to 2024, and to examine their relationship with the Human Development Index (HDI). Using a descriptive quantitative method, the research employed secondary data from the Central Bureau of Statistics (BPS) and UNESCO Institute for Statistics (UIS). Data analysis showed that all six provinces in Sulawesi experienced an increase in educational participation and human development, with North Sulawesi achieving the highest HDI growth (from 69.96 to 75.03), while Gorontalo remained below the regional average (65.17 to 71.23) due to infrastructural and socio-economic constraints. The average Gross Enrollment Rate exceeded 100%, and the Net Enrollment Rate ranged between 91–99%, reflecting broad access yet persistent efficiency issues such as grade repetition and age mismatch. The study concludes that economic capacity, infrastructure, and local policy alignment significantly influence educational equity. Strengthening data-based planning, inclusive support for marginalized groups, and improving teacher quality are recommended strategies to enhance meaningful participation and achieve Sustainable Development Goal 4 (Quality Education).